Experimental Study on Pile-Soil Interaction Response in Saturated Sand under Long-Term Horizontal Cyclic Loading - Lei Xing; Duoyin Wang; Li Wang; Meiling Fan; Lunliang Duan (Advances in Civil Engineering)
To explore the pile-soil interaction response in saturated sand under long-term horizontal cyclic loading, a series of indoor 1 g model tests were carried out with self-made loading equipment. In this paper, the self-made loading system and test program are introduced firstly. Then, the long-term horizontal cyclic loading-induced pile top cumulative displacement, the rotation angle, the mono-pile horizontal cyclic stiffness, the cyclic p-y curve, the pore water pressure, the soil settlement, and cracks around mono-pile are fully studied. Based on the experimental results, the pile-soil interaction response shows a two-stage characteristic with the change in cycle (N), and the short-term effects of horizontal cyclic loading are greater than the long-term effects. In the first 1000 cycles, the cumulative displacement of pile top, the rotation angle of mono-pile, and the pore water pressure could reach more than 90% of the final value. In addition, the cyclic p-y curve obtained by the test is generally smaller than the p-y curve calculated from the API specification, and the soil near the mono-pile will settle with annular cracks under the cyclic loading.